Anti-HIV Tigliane Diterpenoids from Wikstroemia scytophylla - Otsuki, Kouharu; Zhang, Mi; Yamamoto, Asuka; Tsuji, Minami; Tejima, Miyuko; Bai, Zi-Song; Zhou, Di; Huang, Li; Chen, Chin-Ho; Lee, Kuo-Hsiung; Li, Ning; Li, Wei; et al. (Journal of natural products (Washington, D.C.), 2020)
During a chemical investigation of Wikstroemia scytophylla, three new [wikstrocins A–C (1–3)] and three known tigliane diterpenoids (4–6) were isolated. The structures of the new compounds were elucidated from extensive physiochemical and spectroscopic analysis. The correlations between the ECD Cotton effects and B ring structures of tiglianes were also evaluated. The isolated compounds were assessed for their anti-HIV activity against HIV-1 infection of MT4 cells, and two compounds (4 and 6) showed potent anti-HIV activity with IC50 values of 3.8 and 12.8 nM, respectively.